ACUTE REPEATED WINGATE STYLE HIIT EXERCISE IN HYPOXIC CONDITIONS DOES NOT ALTER OXIDATIVE STATUS IN UNTRAINED MEN - Akgul, Mustafa Sakir; Gurses, Veli Volkan; Karabiyik, Hakan; Yavuz, Omer; Taskin, Halil; Koz, Mitat; Devrim, Erdinc (Univ Ljubljana, 2022)
Both high-intensity interval training and training in hypoxic conditions have gained popularity in recent years due to their cardiorespiratory and metabolic benefits. Recent studies focus on the combined effects of both factors in detail. But there is still a scientific gap in the literature on the effects caused and its magnitude in response to this type of training. Therefore, this study aims to investigate the acute effects of Repeated Wingate Style HIIT applied in hypoxic and normoxic conditions on oxidant and antioxidant indicators of recreationally active men. Sixteen participants were randomly assigned to normoxic or hypoxic groups and then they were completed a wingate style 30s*4rps*4 min (sprint time * repeats * recover between sprints) HIIT on normoxic and hypoxic conditions (2500m, FiO2: 0.130) in the normobaric environment. The normality assumption calculated using a Shapiro-Wilk test to ensure the normal distribution of the quantitative for all data (p < 0.05). To analyze differences in baseline data between groups an Independent Sample t -test was performed. The Two-way analysis of variance was used in repeated measurements to reveal the effects of training under hypoxia and normoxia conditions (time, time x group interactions) oxidant and antioxidants. The activities of blood oxidant and antioxidant did not change significantly after training in the hypoxic and normoxic group. As a result, repeated Wingate style HIIT applied in hypoxic and normoxic conditions, did not change both MDA (p=0.79), which is an indicator of oxidant stress, and SOD (p=0.46), CAT (p=0.26), and GSHPX (p=0.17), which are general indicators of antioxidant defense.
Keywords: high intensity interval training; hypoxia; oxidative status